External Factors Causing Students’ Difficulties in Listening - Kartika Pratiwi; Erna Andriyanti (Journal of English Language Teaching and Linguistics, 2019)
To become a good speaker, one has to be a good listener because naturally people cannot speak properly before listening first. Listening is an important requirement, and also a basic competence to be a good speaker in English. Listening is not an easy process since one who listens must be able to distinguish between sounds, understand the vocabulary and grammatical structures, as well as interpret the meaning at the same time. Listening in English requires focus and attention yet, in fact, many students tend to have several difficulties to focus in listening practice. The article aims to show the external factors affecting the students’ difficulty within each process of listening comprehension. The external factors include the speaker, the context of material, and the physical setting. By adopting qualitative design, it is found that the external factors have the higher potential to influence the students’ focus negatively than the students’ physical condition and behavior which are known as internal factors. Moreover, through several findings based on the library research, it is revealed that the external factors are linked to each process of listening. Suggestions with the effective ways to resolve the difficulties in listening are provided.